RNF20/RNF40 supports the aggressive behavior in cervical cancer by regulating a peroxisome-based anti-ferroptotic mechanism - Jansari, Shaishavi; Blandau, Anna; Prokakis, Evangelos; Grimm, Daniela; Naßl, Anja Maria; Küffer, Stefan; Möbius, Wiebke; Dullin, Christian; Ramos-Gomes, Fernanda; Schüürhuis, Leona; Fritsche, Lena; Schridde, Laura; et al. (Cell communication and signaling, 2025)
Background Cervical cancer is the fourth most common cancer entity in women worldwide. Currently, malignant lesions are clinically managed by surgery, conventional chemotherapy, and/or radiotherapy. However, a significant fraction of patients with cervical cancer does not respond to such treatments, highlighting the need for personalized targeted therapies. Histone 2B monoubiquitination (H2Bub1) is an epigenetic marker catalyzed by the RNF20 and RNF40 heterodimeric E3 ligase complex and is strongly involved in the regulation of gene expression. Despite its wellestablished significance in various malignant diseases, the role of RNF20 and RNF40 in cervical cancer remains poorly understood. - Methods We investigated the role of RNF20 and RNF40 in cervical cancer cells by leveraging paraffin-embedded IHC staining on patient material, in vitro functional assays, in vivo CAM assays, flow cytometry, various microscopy-based techniques, ChIP-qPCR, as well as genome-wide transcriptome analysis from cell lines and publicly available datasets. - Results We showed that high RNF20 and RNF40 levels correlate with cervical cancer cell aggressiveness and poor patient prognosis. In addition, pathway enrichment analyses identified that the RNF20/RNF40/H2Bub1-axis positively regulates the peroxisome function. Peroxisomes play a key role in lipid metabolism and the homeostasis of reactive oxygen species. Loss of RNF20 and RNF40 leads to downregulation of peroxisome-related genes such as PRDX5, PEX6, and PMVK, and thus impaired peroxisomal biogenesis, ROS metabolism, and increased lipid peroxidation, ultimately resulting in ferroptotic programmed cell death induction. - Conclusion Together, our results indicate that interfering with RNF20 and RNF40 driven H2Bub1 and the peroxisome transcriptional program could provide a novel target for a therapeutic approach against aggressive cervical cancer. RNF20/RNF40 supports the aggressive